Effect of opening with various size and location on RC deep beam - Siow, Sin Yang (2015)
This study is about analysis of the behaviour of the reinforced concrete deep beam with different sizes of opening and different location of the opening by using ANSYS. The opening on RC deep beam is made for the mechanical and electrical purposes. Before the opening is made, it is important to know the optimum size and its location in order to prevent structural failure. The main objective of this study is to determine the effect of the opening size and its location on the reinforced concrete deep beam in terms of crack pattern and deflection. The study is conducted by using ANSYS 12.0. In this study, there are 7 models. There is one solid beam (DBS), three beams with different size of opening namely DBO1, DBO2 and DBO3, and three beams with opening but different location were designated as DBL1, DBL2 and DBL3. The three point test was used for the analysis. The loading used for the analysis is axial load. The deflection and the crack pattern obtained from the ANSYS were used for discussion. Based on the result, the deflection of the RC deep beam was increase in 31.2% as the opening size increase in 60%. For the different location of opening, as the location of opening move from 350mm to centre of the RC deep beam, the deflection of the RC deep beam was increased in 31.8%. In conclusion, the most appropriate location of the opening on RC deep beam is the place where far away from the loading